Application effect of seminal plasma, GnRH and follicular ablation on the ovarian dynamic in llamas (Lama glama) - Silva H., Nancy (2020)
The study aimed to evaluate the effect of applying seminal plasma, a GnRH analogue and follicular ablation on the follicular dynamic in llamas. The study was carried out in Puno, Peru, using 24 llamas selected under the criterion of presenting a preovulatory follicle >7 mm, determined by transrectal ultrasound. The animals were randomly distributed into four groups: T1, 1 ml PBS IM; T2, 2 ml seminal plasma IM; T3, 1 ml GnRH IM; T4, follicular ablation. The animals were evaluated, by transrectal ultrasound, every 2 h between 20 and 36 h post-treatment to determine ovulation; subsequently daily until day 9 and then every 2 days until day 15 post-stimulation to determine the interval to the emergence of a new follicular wave, the appearance of the new dominant follicle and the diameter of the corpus luteum on day 8 of treatment. No significant difference (p<0.05) was found between treatments in the variables under study. It is possible that there are other factors that could affect the interval to the emergence of a new follicular wave.